Immune response induced by conjunctival immunization with polymeric antigen BLSOmp31 using a thermoresponsive and mucoadhesive in situ gel as vaccine delivery system for prevention of ovine brucellosis - Díaz, Alejandra Graciela (2016)
Control of ovine brucellosis with subcellular vaccines can solve some drawbacks associated with the use of Brucella melitensis Rev.1. Previous studies have demonstrated that the polymeric antigen BLSOmp31 administered by parenteral route was immunogenic and conferred significant protection against B. ovis in rams. Immunization with BLSOmp31 by conjunctival route could be efficient for the induction of mucosal and systemic immune responses. In this work, we evaluated the conjunctival immunization using a thermoresponsive and mucoadhesive in situ gel composed of Poloxamer 407 (P407) and chitosan (Ch) as vaccine delivery system for BLSOmp31 in rams. Serum samples, saliva, lacrimal, preputial and nasal secretions were analyzed to measure specific IgG and IgA antibodies. Cellular immune response was evaluated in vivo and in vitro. Immunization with BLSOmp31-P407-Ch induced high IgG antibody levels in serum and preputial secretions which remained at similar levels until the end of the experiment. Levels of IgG in saliva, lacrimal and nasal secretions were also higher compared to unvaccinated control group but decreased more rapidly. IgA antibodies were only detected in nasal and preputial secretions. BLSOmp31-P407-Ch stimulated a significant cellular immune response in vivo and in vitro. The induction of systemic and local immune responses indicates a promising potential of P407-Ch for the delivery of BLSOmp31 by conjunctival route.